Estudio sobre la legalidad del uso de cannabis medicinal en la legislación ecuatoriana - Jiménez Urresta, Joel Mateo (2024)
What are the gaps in the regulatory framework for medicinal cannabis in Ecuador and how do these affect access, quality and safety of treatments for patients with catastrophic diseases? Around this question, the present research aims to analyze the regulation of cannabis in Ecuador and its impact on the quality of life and treatment of people to demonstrate the need for knowledge about its legality in the Ecuadorian context. A non-experimental descriptive design was used in the first stage and explanatory in the second. The socio-legal research method was chosen, analyzing the social problems that affect the regulation of cannabis. The mixed approach was applied, complementing qualitative-quantitative data to obtain a holistic vision. The following techniques were used: bibliographic research\; case study of Constitutional Court Judgments on the subject in the international and Ecuadorian context\; interviews 4 companies related to cannabis in Ecuador under non-probabilistic convenience sampling\; and surveys of an intentional non-probabilistic sample of 384 patients from the Eugenio Espejo Hospital in Quito with catastrophic illnesses due to being potential users of medicinal cannabis. Despite the development of Ecuadorian legislation and the industry in relation to the use of medicinal cannabis due to the positive impact on the quality of life of users, the regulatory and educational apparatus on the subject must be strengthened for the protection of public health and patient safety.